(untitled) (Journal of the College of Basic Education, 2022)
The problem of feeling remorse is one of the oldest psychological states experienced by the human psyche, and yet it has not received in-depth scientific study like other fields in psychology, just as the subject of situational remorse has not received the attention of researchers in the field of education and psychology, and the increase in the number of individuals who feel remorse has made The topic is vital, so the current research targeted:1- Identifying situational remorse among students of the Department of Psychological Counseling and Educational Guidance.2- Identifying the significance of differences in situational remorse among students of the Department of Psychological Counseling and Educational Guidance according to a variable: A- Gender (males - females).B - Stage (first stage - fourth stage).